Asymmetry Thermal Analyses of Self-Supporting Friction Stir Welding - Li, Zenglou; Li, Chong; Li, Shuohan; Yin, Demeng; Qi, Zhenguo; Tian, Yalin (Frontiers in Materials, 2022)
Due to the inherent issue of requiring rigid back support, friction stir welding (FSW) has serious limitations for welding hollow structures. Self-supporting friction stir welding was proposed to join hollow aluminum extrusions, which could reduce the hindrance of the welding tool and the requirement of rigid back support. In this paper, finite element modeling analyses were carried out for the asymmetric temperature field in the process of self-supporting FSW. The peak temperature of the stir zone appeared in the upper shoulder affected zone, followed by the lower shoulder affected zone. In the upper shoulder affected zone, a peak temperature was not shown at the center of the curve due to the positive correlation between heat generation and radius and different heat dissipation rates. Considering the influence of thermal input and rotation speed on joint formation, 200 mm/min travel speed and 800 rpm rotation speed are the most proper parameters for 5-mm-thick 6082-T6 aluminum alloy self-supporting FSW butt welds.